Chitosan microspheres-supported palladium species as an efficient and recyclable catalyst for Mizoroki–Heck reaction. (12th July 2017) - Shao, Linjun; Qi, Chenze
Abstract : Chitosan microsphere supported palladium catalysts prepared by electrospraying were very active and stable to catalyze the Mizoroki–Heck reaction. Abstract : Chitosan microspheres-supported palladium catalysts (Pd@CM) for Mizoroki–Heck reaction have been successfully prepared by electrospraying PdCl2 /chitosan mixture in a trifluoroacetic acid (TFA) aqueous solution. Swelling capacity measurement and thermal analysis demonstrated that the palladium species in the chitosan microspheres could cross-link the chitosan efficiently. FT-IR spectra demonstrated that the chitosan in the microspheres could be cross-linked by glutaraldehyde, and the formed Schiff bond could chelate the palladium species efficiently. High resolution transmission electron microscopy (HR-TEM) indicated that the entrapment of palladium species in chitosan microspheres could enhance its dispersion. Mizoroki–Heck reaction catalysis results demonstrated that the catalytic activity of Pd@CM was associated with the size of chitosan microspheres. The Pd@CM with a suitable size was even more active than the catalyst with palladium species adsorbed on the surface of chitosan microspheres (Pd-CM). Moreover, the entrapment of palladium species in chitosan microspheres could reduce its aggregation and leaching in the catalysis procedure, which in turn increased the reusability of Pd@CM catalyst. The high catalytic activity and stability of Pd@CM have been attributed to the entrapment of palladium species within the cross-linked chitosan microspheres and the chelation of palladium species with the abundant amine and hydroxyl groups on chitosan chain.